Employee-Driven Innovation: An Intervention Using Action Research - Mats Holmquist; Anna Johansson (Technology Innovation Management Review, 2019)
This article describes an intervention to design and test a method for employee-driven innovation and a model for learning among managers and development leaders. The empirical basis for the intervention focused on personal assistants in the home service within a municipality in Sweden. The intervention was carried out using action research in on a series of workshops with a group of employees, managers, development leaders. Using a “stage” and “stands” theatre metaphor, employees engaged in collective, innovative learning “on the stage” combined with observations and reflections from managers and development leaders “in the stands”. This article contributes a method that can generate creative ideas among the employees and a model that can stimulate experience-based learning through observations. The intervention also shows that action research can be used to develop and test methods and models.